Avaliação do bem-estar dos eqüinos de cavalaria da Polícia Militar de Minas Gerais: indicadores etológicos, endocrinológicos e incidência de cólica. - Baity Boock Leal (2007)
The aim of this study was to evaluate equines welfare undergone to different types of work, housing and handling through behavioural and endocrinological parameters and colic occurences. 116 horses were used, divided into four groups: stabled in stall of 6,25m2 without bedding and which worked on an exclusive urban patrolling (RCAT 1); stabled in stalls of 16 m2 with sawdust bed and performed mainly equine therapy and sports (RCAT 2); semi-stabled in stalls of 6,25m2 without bed and carried out exclusively urban patrolling (PAMP) and the fourth group of animals that were handled within extensive rules, kept free, without work (FLOR). During behavioural observe of stabled horses, higher behavioral disturbances were noticed if compared to the ones kept free. Concerning endocrinological evaluation of seric concentrations of insulin and total tiroxin (TT4), the four groups were within the references values. In relation to cortisol, they were higher in group RCAT 1, followed by the group RCAT 2 and PAMP if compared to group FLOR. Cortisol circadian rhythm was also decreased on stabled animals confirming the occurrence of chronic stressing condition. Incidency of colic occurrences were higher on stabled horses than with free handling ones. Taking the results in account, it can be concluded therefore, that cavalry stabled horses that perforrm urban patrolling activities have their welfare compromised in relation to animals kept free at pickets, country enviroment and without patrolling activity. These mentioned animals have higher probability of developing behavioural disturbances and colic occurrences.